Consumer psyche and positioning strategies - Shrafat Ali Sair (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The significance of positioning is firm in marketing but there is scant research, how positioning (strategies) alternatives are important or substitute each other, which positioning strategy overlap and how it measures effectively. Sometimes brand managers waste their energies and company resources to build an image of brand with simultaneous positioning strategies, whereas purpose can be achieved by applying the one of them. Quantitative mode of study is applied herein the research. Relative effectiveness of positioning strategies is measure by using multidimensional scale. The scale is based on four dimensions i.e., favorability, dissimilarity, uniqueness, and credibility. The associated items are seventeen with these four dimensions. Two print advertisements from cellular industry that are representing the given positioning strategies showed to the 100 consumers using purposive sampling technique. The statistical technique, ANCOVA is applied herein the study. The results show that the surrogate positioning strategy and feature positioning are identical in term of favorability and credibility. Other two dimensions named dissimilarity and uniqueness counter balance each other.
Keywords: 330; positioning; positioning strategy; surrogate positioning; feature positioning